ADGRG1 Is a Predictor of Chemoresistance and Poor Survival in Cervical Squamous Carcinoma - Zhang, Shuo; Guo, Kui; Liang, Ying; Wang, Kun; Liu, Shuyan; Yang, Xingsheng (Frontiers in Oncology, 2021)
Background: Cisplatin is the first-line chemotherapy for cervical cancer. Cisplatin resistance has always been one of the most significant barriers to acquiring better outcomes. However, the complex molecular mechanisms accounting for the phenomenon are not completely clear. Methods: Construction of the cisplatin-resistant cell model of cervical cancer, then perform RNA sequencing and bioinformatic analysis of the differential expression genes. Then Adhesion G protein-coupled receptor G1 (ADGRG1) was screened out as our target gene. Gene Expression Profiling Interactive Analysis (GEPIA) was searched to show the expression level of ADGRG1 in cervical cancer and normal tissue. Kaplan-Meier Plotter (Kmplot) was used to explore the relationship of its expression with survival data. Tissue specimens were used to verify the relationship between the clinicopathological characteristics and ADGRG1 expression. Then we explored the roles of ADGRG1 in tumorigenesis through in vitro and in vivo assays. Results: We found the ADGRG1 was significantly overexpressed in cervical cancer tissues compared to corresponding normal tissues. Higher ADGRG1 expression was correlated with poor progress-free survival. Knockdown of ADGRG1 markedly suppressed cell proliferation, migration, invasion and increased cell sensitivity to cisplatin in vitro. Similarly, the role of ADGRG1 knockdown on tumorigenicity and sensitivity to cisplatin treatment was verified in vivo. The underlying mechanism was explored by western blotting that ADGRG1 knock-down inhibited tumorigenesis by PI3K/Akt/mTOR signaling pathway. Conclusion: ADGRG1 acts as an oncogene to maintain tumorigenicity, migration, and invasion and its depressed expression prompts sensitivity to cisplatin. Thus ADGRG1 may represent a potential prognostic marker and possible therapeutic target for cervical cancer. Keywords: ADGRG1, Cisplatin resistance, Proliferation, PI3K/Akt pathway, Cervical cancer